2014
DOI: 10.1007/s00894-014-2342-1
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on diastereoselective oxidative dearomatization by iodoxybenzoic acid

Abstract: The reaction mechanism of diastereoselective oxidative dearomatization by iodoxybenzoic acid of key compounds involved in the total synthesis of epicocconone analogs, which are efficient fluorophores with a wide range of applications in protein staining and separation, was studied using density functional theory. In particular, the conformational space was investigated, as was the role of the so-called hypervalent twist move, which is thought to be the rate-determining step. Both kinetic and thermodynamical as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Both STE and KTE are frequently epitomised by square planar complexes, with a d 8 electronic configuration of the metal cation, 5 and octahedral complexes, with either a d 6 or d 0 metal electronic configuration. 6 More rarely, they can be observed for lanthanide, 7 actinide 8,9 or even iodine 10,11 complexes. These two effects are known to be a likely cause of several chemical properties, ranging from catalytic activity and selectivity [12][13][14] to metalloprotein reactivity [15][16][17][18] and anti-tumoral activity.…”
Section: Introductionmentioning
confidence: 99%
“…Both STE and KTE are frequently epitomised by square planar complexes, with a d 8 electronic configuration of the metal cation, 5 and octahedral complexes, with either a d 6 or d 0 metal electronic configuration. 6 More rarely, they can be observed for lanthanide, 7 actinide 8,9 or even iodine 10,11 complexes. These two effects are known to be a likely cause of several chemical properties, ranging from catalytic activity and selectivity [12][13][14] to metalloprotein reactivity [15][16][17][18] and anti-tumoral activity.…”
Section: Introductionmentioning
confidence: 99%
“…A hypervalent twist, defined as coordinated motion of an oxo group and an anionic ligand, is thus necessary to generate a stable intermediate ( 8 ) and is followed by reductive elimination involving cleavage of the C–H bond. Goddard’s work concluded that the hypervalent twist is the RDS, and this prediction has influenced subsequent research. , However, it is known that the exchange between the apical and the equatorial ligands is an easy process in both λ 3 - and λ 5 -iodanes . More importantly, the hypervalent twist does not involve C–H bond cleavage, and this seems inconsistent with Corey’s KIE experiment.…”
mentioning
confidence: 99%
“…17 Same conclusion has been drawn later by other researchers using various functionals with basis sets similar to LACV3P**. [18][19][20][21] However, this conclusion is inconsistent with the Corey's kinetic isotope effect (KIE) experiments. 22 In 2017, our theoretical study employing a wide range of basis sets at the level of both DFT and density cumulant theory (DCT) revealed that the RDS of IBX-mediated oxidation is strongly sensitive to the choice of basis sets.…”
Section: Introductionmentioning
confidence: 84%
“…Earlier density functional theory (DFT) study 15 determined the hypervalent twist as the RDS using the MPW1K functional and the LACV3P** basis set, 16 which is a combination of Pople's 6‐311G** basis set 14 and the LANL2DZ effective core 17 . Same conclusion has been drawn later by other researchers using various functionals with basis sets similar to LACV3P** 18–21 . However, this conclusion is inconsistent with the Corey's kinetic isotope effect (KIE) experiments 22 …”
Section: Introductionmentioning
confidence: 99%